DARAPLADIB INHIBIT ADHESION MOLECULE EXPRESSION IN AORTA AT EARLY STAGES OF ATHEROSCLEROSIS USING SPRAGUE-DAWLEY TYPE 2 DIABETES MELLITUS MODEL - T, Heriansyah; H, Hanifa; S, Andarini; Andri, Wihastuti Titin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Hyperglycemia and hyperlipidemia in diabetes mellitus (DM) can lead an atherosclerosis. The increase of low-density lipoprotein level in DM and atherosclerosis is correlated with lipoprotein-associated phospholipase A2 (Lp-PLA2). Lp-PLA2 is an enzyme that produces lysophosphatidylcholine (LysoPC) and oxidized nonesterified fatty acids. LysoPC regulated inflammation mediators, include cytokines, adhesion molecules (such as vascular cell adhesion molecule-1 [VCAM-1] and intercellular adhesion molecules-1 [ICAM-1]), and monocyte chemoattractant protein-1 (MCP-1) chemotactic. Darapladib is known as a Lp-PLA2 specific inhibitor. It is also considered to be an atherosclerosis treatment. The aim of this study is to know darapladib effect on VCAM-1 and ICAM-1 aorta expression in early stages of atherosclerosis using Sprague-Dawley Type 2 DM (T2DM) model. Methods: About 30 Spraque-Dawley rats are divided into three main groups: Normal, T2DM, and T2DM with darapladib administration group. Each group consists of 2 serials treatment time: 8 and 16 weeks treatment group. Fasting blood glucose, resistance insulin, and lipid profile were measured and analyzed to ensure T2DM model. VCAM-1 and ICAM-1 expression were measured using double staining immunofluorescence. Each data were analyzed using one-way ANOVA. Results: There is a significant difference in VCAM-1 expression in T2DM group (8 and 16 weeks), with p=0.011 and 0.034 (p<0.05), respectively. Mean while, a significant difference for ICAM-1 only showed in 8 weeks T2DM group with p=0.03 (p<0.05). Moreover, there is a decreasing trend in 16 weeks T2DM group. Conclusion: Our results showed that darapladib can decrease VCAM-1 and ICAM-1 aorta expression in early stages of atherosclerosis using Sprague- Dawley T2DM model. This showed another evidence of darapladib as atherosclerosis treatment.